Preparation method of multifunctional bioactive composite hydrogel based on nanoparticles

By preparing a multifunctional bioactive composite hydrogel based on nanoparticles, the problems of poor stability and great toxicity of the hydrogel are solved, and a dual crosslinking network structure hydrogel with high mechanical strength and biocompatible are achieved, which significantly accelerates the wound healing speed.

CN119909005APending Publication Date: 2025-05-02YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510168582.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, hydrogels have poor stability and high toxicity, which are prone to bacterial infection, limiting their application in chronic wound healing.

Method used

By preparing a multifunctional bioactive composite hydrogel based on nanoparticles, Co-ZIF-8 nanoparticles are cross-linked with oxidized sodium alginate and carboxymethyl chitosan to form a hydrogel with a dual crosslinking network structure, enhancing its mechanical properties and biocompatibility.

Benefits of technology

The high mechanical strength, stability and biocompatibility of the hydrogel are achieved, the rapid release and cytotoxicity of nanoparticles are avoided, and the wound healing speed is significantly accelerated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909005A_ABST
    Figure CN119909005A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: dissolving 2-methylimidazole, Zn (NO3) 26H2O and Co (NO3) 26H2O in a DMF-methanol solution, fully reacting to obtain Co-ZIF-8, carrying out ultrasonic dispersion on the Co-ZIF-8, adding curcumin, stirring and centrifuging to obtain CMM-Co-ZIF-8, mixing a suspension of SA and absolute ethyl alcohol with a NaIO4 aqueous solution, carrying out ultrasonic dispersion, adding curcumin, stirring and centrifuging to obtain CMM-Co-ZIF-8, carrying out ultrasonic dispersion on the CMM-Co-ZIF-8, carrying out ultrasonic dispersion on the CMM-Co-ZIF-8, and carrying out ultrasonic dispersion on the CMM-Co-ZIF-8 to obtain the nano-particle-based multifunctional bioactive composite hydrogel. The preparation method comprises the following steps: carrying out a reaction in the dark at room temperature, adding ethylene glycol to terminate the reaction, standing in absolute ethyl alcohol for precipitation, and dialyzing in a dialysis bag to obtain OSA, carrying out a cross-linking reaction on OSA and CMCS to form a stable cross-linked structure, wrapping CMM-Co-ZIF-8 in the stable cross-linked structure to form CCZ-coated OSA / CMCS hydrogel, spraying tannic acid to the CCZ-coated OSA / CMCS hydrogel, and carrying out secondary enhancement to obtain the CCZ-coated OSA / CMCS hydrogel. The curcumin-loaded hydrogel CCZ-coated OSA / CMCS / TA with a double-crosslinked network structure is obtained, the prepared CCZ-coated OSA / CMCS / TA slowly controls the release rate of CMM-Co-ZIF-8, has good stability, reduces potential toxicity, achieves the synergistic treatment effect of resisting inflammation, bacteria and oxidation, and is applied to the field of biomedicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanocomposite hydrogels, and in particular to a method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles. Background Art

[0002] Delayed healing of chronic wounds poses a major challenge to human health, affecting approximately 1-2% of the global population and resulting in more than $31 billion in medical costs each year. Once a wound occurs, bacterial infection may trigger a persistent inflammatory response. In this inflammatory environment, the increase in free radicals (reactive oxygen species, ROS) can lead to further tissue damage and a sustained inflammatory state. Therefore, excessive production of free radicals and excessive inflammatory responses are key factors in the slow healing of chronic wounds. Due to their excellent biocompatibility and high absorbability, hydrogel dressings have become one of the preferred materials for the treatment of chronic wounds. Nanoparticles, such as metal oxides and materials containing catalytic cores, can mimic the catalytic function of natural enzymes and effectively regulate ROS levels in wounds due to their unique physicochemical properties.

[0003] In the prior art, for chronic wounds, some nanoparticles with therapeutic effects are directly applied to the wounds, but their therapeutic effects may be limited by insufficient bioavailability and biocompatibility. In addition, the rapid release of nanoparticles in the wound environment may lead to excessive local concentrations, thereby generating cytotoxicity, limiting their clinical application. Moreover, most therapeutic hydrogels have disadvantages such as poor stability and self-toxicity. Summary of the invention

[0004] The present invention aims to solve the technical problems in the prior art that hydrogels have poor stability, high self-toxicity and are prone to bacterial infection, and provides a method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles with good stability, reduced potential toxicity and not prone to bacterial infection.

[0005] The object of the present invention is achieved by a method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles, comprising the following steps: (1) Preparation of Co-ZIF-8: Dissolve appropriate amounts of 2-methylimidazole, Zn(NO3)2∙6H2O and Co(NO3)2∙6H2O in a DMF-methanol solution and allow to react fully to obtain a cobalt-doped imidazole-based zeolite framework, namely Co-ZIF-8; (2) Preparation of CCM-Co-ZIF-8: Ultrasonic dispersion of the Co-ZIF-8 prepared in step (1), adding curcumin, stirring and centrifuging, and collecting the precipitate to obtain curcumin-loaded Co-ZIF-8, i.e., CCM-Co-ZIF-8; (3) Preparation of OSA: A suspension of SA and anhydrous ethanol is mixed with a NaIO4 aqueous solution, and the mixture is first reacted at room temperature in the dark, and then ethylene glycol is added to terminate the reaction to obtain a reaction mixture. The reaction mixture is then allowed to stand and precipitate in anhydrous ethanol, dialyzed in a dialysis bag, the dialyzate is collected, and freeze-dried to obtain oxidized sodium alginate, i.e., OSA. (4) Preparation of CCZ@OSA / CMCS hydrogel: OSA prepared in step (3) was mixed with carboxymethyl chitosan, and after cross-linking reaction, CCM-Co-ZIF-8 prepared in step (2) was added to obtain CCZ@OSA / CMCS hydrogel; (5) Preparation of CCZ@OSA / CMCS / TA: Spraying tannic acid onto the CCZ@OSA / CMCS hydrogel prepared in step (4) to obtain CCZ@OSA / CMCS / TA.

[0006] Furthermore, step (1) specifically includes the following sub-steps: (1.1) DMF and methanol are mixed in a ratio of 4:1 to prepare a DMF-methanol solution, and 2-methylimidazole is dissolved in the DMF-methanol solution to obtain a 2-methylimidazole solution; (1.2) Dissolve Zn(NO3)2∙6H2O and Co(NO3)2∙6H2O in a DMF-methanol mixture to obtain a mixed solution; (1.3) Mix the 2-methylimidazole solution prepared in step (1.1) with the mixed solution prepared in step (1.2), stir at a speed of 500 to 1000 rpm, and after sufficient reaction, centrifuge to obtain the precipitate, then wash it with methanol at least 3 times, and dry it to obtain Co-ZIF-8 for standby use.

[0007] Furthermore, in step (2), the CCM-Co-ZIF-8 preparation method is as follows: pour the Co-ZIF-8 prepared in step (1.3) into anhydrous methanol, ultrasonically disperse it to obtain a Co-ZIF-8 dispersion, then add CCM to the Co-ZIF-8 dispersion, stir evenly, wash it with anhydrous methanol and dry it to obtain CCM-Co-ZIF-8.

[0008] Furthermore, step (3) specifically includes the following sub-steps: (3.1) SA is dispersed in anhydrous ethanol and stirred to form a suspension. NaIO4 in an amount equal to that of SA is added to pure water and fully dissolved to obtain a NaIO4 solution. Subsequently, the suspension is mixed with the NaIO4 solution and reacted in the dark at room temperature for 5 to 6 hours. Ethylene glycol in an amount equal to that of NaIO4 is added to terminate the reaction to obtain a reaction mixture; (3.2) The reaction mixture of step (3.1) was poured into anhydrous ethanol and allowed to stand for precipitation. The supernatant was discarded, and the lower precipitate was placed in a dialysis bag with a molecular weight cutoff of 3500Da and dialyzed for at least 3 days. The dialysate was collected and freeze-dried to obtain OSA.

[0009] Furthermore, step (4) specifically includes the following sub-steps: (4.1) preparing a carboxymethyl chitosan solution with a concentration of 0.1 g / mL, and mixing the OSA prepared in step (3.2) with the carboxymethyl chitosan solution in a mass ratio of 1:(1 to 1.5) to obtain an OSA-CMCS hydrogel; (4.2) Prepare a CCM-Co-ZIF-8 solution with a concentration of 100 ug / mL, and mix it evenly with the OSA-CMCS hydrogel prepared in step (4.1) at a mass ratio of 1:1 to obtain a hydrogel loaded with CCM-Co-ZIF-8, namely, CCZ@OSA / CMCS hydrogel.

[0010] Furthermore, in step (5), the CCZ@OSA / CMCS / TA hydrogel preparation method comprises spraying 2.5%-5% tannic acid by mass onto the CCZ@OSA / CMCS hydrogel prepared in step (4.2), and after sufficient reaction, obtaining a hydrogel having a double cross-linked network structure loaded with curcumin, namely, CCZ@OSA / CMCS / TA hydrogel.

[0011] Furthermore, the mass ratio of the Co-ZIF-8 dispersion to CCM is 1:(1-3).

[0012] Furthermore, in step (1.2), the mass ratio of Zn(NO3)2∙6H2O to Co(NO3)2∙6H2O is 1:(1-1.5).

[0013] Furthermore, in step (1.3), the volume ratio of the 2-methylimidazole solution to the mixed liquid is 1:(1-1.5).

[0014] The present invention also provides use of the hydrogel in preparing a chronic wound healing medicament.

[0015] The present invention utilizes Zn(NO3)2·6H2O and Co(NO3)2·6H2O to dissociate in DMF-methanol solution to release Zn 2+ and Co 2+ ions, 2-methylimidazole as ligand, and Zn 2+ and Co 2+ Ion coordination, through the connection of imidazole rings, forms a three-dimensional porous structure of zeolitic imidazole framework (ZIF), Co 2+ Partially replace Zn 2+The cobalt-doped imidazole zeolite framework, i.e., Co-ZIF-8, is obtained by physically adsorbing or chemically loading curcumin (CCM) into the pores of Co-ZIF-8 to obtain curcumin-loaded Co-ZIF-8 (CCM-Co-ZIF-8). Then, the oxidatively modified sodium alginate (oxidized sodium alginate OSA) is cross-linked with carboxymethyl chitosan (CMCS) to form a stable cross-linked structure (OSA / CMCS). Then, CCM-Co-ZIF-8 is wrapped in the stable cross-linked structure to form a curcumin-loaded hydrogel (CCZ@OSA / CMCS hydrogel). The hydrogel has higher mechanical strength, stability and biocompatibility. Finally, tannic acid is combined with the hydrogel through hydrogen bonds and the like to obtain a curcumin-loaded double cross-linked network structure hydrogel (CCZ@OSA / CMCS / TA), which can also be made into a nano-based The multifunctional bioactive composite hydrogel of the particles further enhances the mechanical properties and biocompatibility of the hydrogel, achieving a secondary enhancement effect; the CCZ@OSA / CMCS / TA hydrogel prepared by the present invention comprises a first-layer network formed by physical or chemical crosslinking of the hydrogel itself, and a second-layer network formed by tannic acid (TA) through hydrogen bonding, hydrophobic interaction, metal coordination and oxidative crosslinking. The two layers of networks are intertwined to form a double-crosslinked network structure, which significantly improves the mechanical properties, stability and functional properties of the hydrogel, and the CCM-Co-ZIF-8 nanoparticles are uniformly dispersed and fixed in the double-network hydrogel, effectively preventing the aggregation and rapid release of the nanoparticles. The sustained-release properties of the hydrogel control the release rate of CCM-Co-ZIF-8, avoiding the cytotoxicity caused by excessive local concentration, and the double-network structure enhances the mechanical strength and chemical stability of the material. In addition, the ZIF-8 framework encapsulates Co ions, reducing their direct exposure, while the anti-inflammatory and antioxidant properties of CCM (curcumin) further reduce potential toxicity. The double-cross-linked network structure enables the hydrogel to achieve the long-term delivery of nanoparticles, achieving multifunctional synergistic therapeutic effects of anti-inflammatory, antibacterial, and antioxidant properties, thereby accelerating the healing of wounds and having applications in the biomedical field. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The physical, chemical and morphological characterizations of the Co-ZIF-8, CCM-Co-ZIF-8 nanoparticles and CCZ@OSA / CMCS / TA of the present invention were performed.

[0017] Figure 2 This is a test diagram of the mechanical properties of the CCZ@OSA / CMCS / TA hydrogel of the present invention.

[0018] Figure 3 Schematic diagram of the antibacterial performance of the CCZ@OSA / CMCS / TA hydrogel of the present invention.

[0019] Figure 4 The CCZ@OSA / CMCS / TA hydrogel of the present invention promotes cell proliferation and migration in vitro.

[0020] Figure 5 This is a test diagram of the antioxidant and anti-inflammatory properties of the CCZ@OSA / CMCS / TA hydrogel of the present invention.

[0021] Figure 6 Schematic diagram comparing the closure process of the wounds of mice infected with Staphylococcus aureus when treated with PBS, OSA / CMCS, CCZ@OSA / CMCS, and CCZ@OSA / CMCS / TA, respectively.

[0022] Figure 7 Schematic diagram of the histomorphological manifestations of wounds after treatment with PBS, OSA / CMCS, CCZ@OSA / CMCS, and CCZ@OSA / CMCS / TA in the present invention. DETAILED DESCRIPTION

[0023] The present invention is further analyzed, explained and compared by means of specific embodiments and comparative examples.

[0024] Example 1 (1) DMF and methanol were mixed in a ratio of 4:1 to form a DMF-methanol solution. 1.16 g of 2-methylimidazole was dissolved in 10 mL of DMF-methanol mixture. At the same time, 0.58 g of Zn(NO3)2∙6H2O and 0.58 g of Co(NO3)2∙6H2O were weighed and dissolved in 15 mL of DMF-methanol mixture. After complete dissolution, the 2-methylimidazole solution was poured into the above mixture and stirred at 500 rpm for 7 h. After stirring, the mixture was centrifuged and washed three times with methanol and centrifuged. After standing and drying, Co-ZIF-8 was obtained.

[0025] (2) Weigh 100 mg of Co-ZIF-8 and place it in 10 mL of anhydrous methanol for uniform ultrasonic dispersion. Then weigh 100-150 mg of CCM and add it. Stir it thoroughly with a magnetic stirrer for 5-30 min, then wash it with anhydrous methanol and dry it to obtain CCM-Co-ZIF-8.

[0026] (3) Disperse 10 g of SA in 100 mL of anhydrous ethanol and stir with a magnetic stirrer to form a suspension. Add NaIO4 (9.89 g) in an amount equal to the amount of SA substance into 100 mL of pure water and fully dissolve. Then, mix the two and react at room temperature in the dark for 6 h. After the reaction is completed, add ethylene glycol (2.37 mL) in an amount equal to that of NaIO4 to terminate the reaction, and continue the reaction for 30 min. Then, pour the reaction mixture into anhydrous ethanol and let it stand for precipitation. After 12 h, discard the supernatant and place the lower precipitate in a dialysis bag (MWCO 3500Da) for dialyzation for 3 days. Finally, collect the dialysate and freeze-dry it to obtain OSA; (4) Prepare 100 ug / mL CCM-Co-ZIF-8 solution, dissolve OSA in the solution to make the OSA concentration 0.1 g / mL. At the same time, prepare 0.1 g / mL CMCS, mix the above solutions in a ratio of 1:1, and obtain CCZ@OSA / CMCS hydrogel; (5) 2.5% TA was sprayed onto the CCZ@OSA / CMCS hydrogel. The phenolic hydroxyl groups of TA formed hydrogen bonds with the amino groups on CMCS through electrostatic interaction, and finally a CCZ@OSA / CMCS / TA hydrogel with a double cross-linked network structure was obtained.

[0027] Example 2 The difference between this embodiment and embodiment 1 is that the masses of Zn(NO3)2∙6H2O and 0.77 Co(NO3)2∙6H2O are 0.77 g respectively, and the 2-methylimidazole solution is poured into the above mixed solution and stirred at a speed of 1000 rpm for 15 h.

[0028] Test Example 1 The Co-ZIF-8 and CCM-Co-ZIF-8 nanoparticles prepared in Example 1 were characterized by Fourier transform infrared spectroscopy (FTIR). Figure 1 As shown in A, Co-ZIF-8 has the peaks at 3135, 2928, 1606 and 1580 cm −1 The characteristic peaks at 1511, 1279, and 1152 cm-1 correspond to aromatic CH stretching, aliphatic CH stretching, CC stretching, and CN stretching. −1 The other peaks observed at 3490 cm-1 are attributed to the C=C stretching of the benzene ring, aromatic CO stretching, and COC stretching. −1 Blue shift to 3426 cm −1 , confirming the encapsulation of curcumin in Co-ZIF-8.

[0029] Figure 1B is the FTIR characterization result of CCZ@OSA / CMCS hydrogel prepared in Example 1. In the OSA / CMCS spectrum, 1420 cm -1 The absorption peak at 1752 cm -1 The absence of the aldehyde absorption peak at 1413 cm indicates that the aldehyde group in OSA has reacted with the amino group on the CMCS molecular chain to form a Schiff base bond. These results indicate that OSA / CMCS hydrogel was successfully prepared. -1 The vibration frequency of TA at 1720 cm -1 and 1615 cm -1 The CO stretching vibration peak at 1444 cm -1 The aromatic ring peak of C=CC is at 1193 cm -1 The CO stretching vibration peak at 1720 cm in CCZ@OSA / CMCS / TA hydrogel -1 The decrease of the vibration peak at 1406 cm in CCZ@OSA / CMCS / TA is due to the formation of an amide bond between the carboxyl group of TA and the amino group of CMCS. -1 The significant weakening of the vibration absorption peak at may be due to the formation of hydrogen bonds. Figure 1 As shown in C, the formed hydrogel has a uniform porous structure.

[0030] Test Example 2 Figure 2 This is a mechanical properties test diagram of CCZ@OSA / CMCS / TA prepared in Example 1. Figure 2 As shown in A, the hydrogel was cut into two parts, one part was dyed red with rhodamine, and after standing for 2 hours, it merged into a single color, indicating that the hydrogel has good self-healing properties. The compression results show that the fracture stress of the hydrogel should be 60 kPa and 132 kPa, indicating that the addition of TA significantly enhanced the compressive strength of the hydrogel bundle. Figure 2 B. Step strain sweep test under strain of 1% and 200%. Under 1% strain, the hydrogel remained in the gel state. Under 200% strain, the hydrogel was completely destroyed. When the high strain was removed, the hydrogel restored its integrity, indicating that the hydrogel has reversible Schiff base bonds. In order to quantitatively evaluate the self-healing properties of the hydrogel, the hydrogel was subjected to small strain (1%) and large strain (200%) step-strain sweep tests ( Figure 2C), the hydrogel maintained its gel state at 1% strain, while it was completely destroyed at 200% strain. After removing the high strain, the hydrogel recovered its integrity, which was attributed to the formation of reversible Schiff base bonds between the aldehyde groups of OSA and the amino groups of CMCS.

[0031] Test Example 3 Escherichia coli and Staphylococcus aureus were used as models of Gram-positive and Gram-negative bacteria.

[0032] Figure 3 The antibacterial performance test results of CCZ@OSA / CMCS / TA hydrogel prepared in Example 1 are as follows: Figure 3 AC shows that the bacterial viability of E. coli and S. aureus in the OSA / CMCS group was about 60%. In contrast, the viability of E. coli and S. aureus in the CCZ and TA groups was significantly reduced, showing signs of decreased viability and some cell death, accompanied by obvious membrane rupture. The bacterial viability of E. coli and S. aureus in the CCZ@OSA / CMCS group dropped to about 10%, while the bacterial viability of the CCZ@OSA / CMCS / TA group was only 3.51% and 2.75%, respectively, showing excellent antibacterial effects.

[0033] Test Example 4 In vitro cell proliferation and migration test: L929 cells were co-incubated with hydrogel to evaluate cell migration ability. L929 cell suspension (about 2×10 cells per well) was added to a 6-well plate. 5 cells), a straight line was drawn in the center of each well using a 200 μL pipette tip, and then 200 μL OSA / CMCS, CCZ@OSA / CMCS, and CCZ@OSA / CMCS / TA hydrogel extracts were added to each well to culture cells. The blank wells without hydrogels were used as the control group. After culturing in a 37 ℃, 5% CO2 incubator for 24 h and 48 h, images were taken using a fluorescent inverted microscope to evaluate the cell migration ability.

[0034] Figure 4 The results of the in vitro cell proliferation and migration promotion test of CCZ@OSA / CMCS / TA hydrogel prepared in Example 1 show that CCZ@OSA / CMCS / TA hydrogel significantly enhances cell proliferation and migration ( Figure 4 A). Figure 4 B The results showed that the remaining area in the CCZ@OSA / CMCS / TA hydrogel group (24.4%) was significantly reduced compared with the control group (82.6%), OSA / CMCS (72.1%), and CCZ@OSA / CMCS (58.5%) groups.

[0035] Test Example 5 Antioxidant and anti-inflammatory performance test: The antioxidant capacity of the hydrogel was evaluated by the scavenging ability of 1,1-diphenyl-2-trinitrophenylhydrazine free radical (DPPH). The total antioxidant capacity assay reagent was used to detect the DPPH-ethanol solution and the 0.1 g / mL hydrogel extract in equal volumes. The blank group was set as 50 µL of extract plus 950 µL of reagent one, and the experimental group was 950 µL of reagent one plus 50 µL of sample. After mixing evenly, the mixture was reacted at room temperature in the dark for 20 min, and 1 mL was taken to measure the absorbance at 515 nm. RAW264.7 cells were treated with lipopolysaccharide (LPS, 5 μg / mL) to evaluate the anti-inflammatory effects of OSA / CMCS, CCZ@OSA / CMCS, and CCZ@OSA / CMCS / TA hydrogels. RAW264.7 cell suspension (about 2×10 5 Each experimental group was set up in triplicate, and the cells were incubated with LPS for 24 hours. Subsequently, 200 μL of OSA / CMCS, CCZ@OSA / CMCS, and CCZ@OSA / CMCS / TA hydrogel solutions were added to the Transwell chamber. After incubation for another 24 hours, the culture medium was aspirated, and 600 μL of Trizol reagent was added to lyse the cells for quantitative detection of the pro-inflammatory cytokine TNF-α.

[0036] Figure 5 The results of the antioxidant and anti-inflammatory properties of the CCZ@OSA / CMCS / TA hydrogel prepared in Example 1 are as follows: Figure 5 As shown in A, CCZ@OSA / CMCS / TA hydrogel has excellent DPPH scavenging ability, with a DPPH scavenging efficiency of 74%, while CCZ@OSA / CMCS has a lower DPPH scavenging rate, which may be due to the lower release of CCZ, but compared with the control group, OSA / CMCS DPPH free radical scavenging rate is still 10% higher. After inducing M1 macrophages with LPS, we performed qPCR analysis on cells treated with OSA / CMCS, CCZ@OSA / CMCS, and CCZ@OSA / CMCS / TA hydrogels to quantitatively detect the secretion of the pro-inflammatory factor TNF-α. Figure 5 As shown in B, the LPS-treated group without any material was used as the control group. In contrast, the expression of pro-inflammatory cytokines was significantly inhibited in the hydrogel-treated group. Notably, CCZ@OSA / CMCS / TA showed the best therapeutic effect by downregulating M1 macrophages. In summary, CCZ@OSA / CMCS / TA hydrogels exhibited a strong anti-inflammatory effect by inhibiting inflammation.

[0037] Test Example 6 Test on the closure process of wounds infected by Staphylococcus aureus in mice: A full-thickness skin wound model infected by Staphylococcus aureus was created in the back area of ​​mice. The mice were randomly grouped according to the experimental requirements and placed in a dust-free laboratory for one week before skin wounds were established. The mice were anesthetized with 1-3% isoflurane inhalation using a small animal anesthesia machine for surgery. The hair on the back of the mice was removed, and holes were drilled in the back of the mice using an 8 mm trephine drill to form two symmetrical holes with a diameter of 8 mm. About 10 7 The animal model was constructed by inoculating Staphylococcus aureus with 100 μg / mL of Staphylococcus aureus. On days 0, 3, 7, and 14, the wound sites of the mice were photographed and weighed.

[0038] Quantitative analysis of the wound surface area in mice. Figure 6 Schematic diagram of the closure process of a wound infected with Staphylococcus aureus in mice. During the wound healing process, the changes in the wound site were macroscopically evaluated at 0, 3, 7, and 14 days ( Figure 6 A, B). At the same time, the wound surface area of ​​mice was quantitatively analyzed ( Figure 6 C). The results showed that the healing effect of the CCZ@OSA / CMCS / TA hydrogel group was significantly better than that of the other groups, with a wound healing rate of 99%, indicating almost complete recovery. In contrast, the healing rates of the OSA / CMCS and CCZ@OSA / CMCS groups were relatively low, at 93% and 96%, respectively. These results indicate that CCZ@OSA / CMCS / TA hydrogel significantly promotes wound healing. The body weight of the mice was recorded throughout the study ( Figure 6 D) All mice grew well, and their weights showed an upward trend after 14 days, indicating that the hydrogel in the experimental group did not affect the normal growth of mice.

[0039] Test Example 7 Histomorphological test of wounds: The wound surface and surrounding tissues were taken 7 and 14 days after surgery, placed at -80 °C, embedded and sliced ​​using a freezing microtome, and the slices were fixed on slides for staining. Finally, histological analysis was performed according to the instructions of the H&E staining kit and the Masson staining kit. In vivo immunofluorescence staining was used to evaluate the polarization of mouse macrophages after treatment. Tissue sections for immunofluorescence staining were first permeabilized with 0.5% Triton X-100 and then blocked with 5% goat serum. Next, the sections were incubated with the primary antibody (CD68, CD163) at a dilution ratio of 1:200 at 4 °C overnight. Subsequently, the secondary antibody (Alexa Fluor 488 and 594, at a dilution ratio of 1:1000) was used for staining at room temperature for 2 h, and the nuclei were counterstained with DAPI. Finally, the samples were fixed on slides with glycerol buffer, and the relevant images were obtained by microscopic photography.

[0040] H&E staining and Masson's trichrome staining effectively visualized the growth of the wound bed, granulation tissue, hair follicles, and collagen deposition. Figure 7 The schematic diagram of the histomorphological performance of the wound is shown as follows: Figure 7 As shown in A, compared with other experimental groups, the CCZ@OSA / CMCS / TA group showed more increase in hair follicles and epidermal cells. At 7 and 14 days, immunofluorescence staining was used to detect the infiltration of macrophage markers (M2 marker CD163) in the wound surface (see Figure 2). Figure 7 B). The control group showed almost no red fluorescence, indicating that CD163 was not expressed. In contrast, the CCZ@OSA / CMCS / TA group had the highest expression of CD163, indicating that CCZ@OSA / CMCS / TA restored the normal function of macrophages and promoted the transition of macrophages from M1 phenotype to M2 phenotype.

Claims

1. A method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles, comprising the following steps: (1) Preparation of Co-ZIF-8: Dissolve appropriate amounts of 2-methylimidazole, Zn(NO3)2∙6H2O and Co(NO3)2∙6H2O in a DMF-methanol solution and allow to react fully to obtain a cobalt-doped imidazole-based zeolite framework, namely Co-ZIF-8; (2) Preparation of CCM-Co-ZIF-8: Ultrasonic dispersion of the Co-ZIF-8 prepared in step (1), adding curcumin, stirring and centrifuging, and collecting the precipitate to obtain curcumin-loaded Co-ZIF-8, i.e., CCM-Co-ZIF-8; (3) Preparation of OSA: A suspension of SA and anhydrous ethanol is mixed with a NaIO4 aqueous solution, and the mixture is first reacted at room temperature in the dark, and then ethylene glycol is added to terminate the reaction to obtain a reaction mixture. The reaction mixture is then allowed to stand and precipitate in anhydrous ethanol, dialyzed in a dialysis bag, the dialyzate is collected, and freeze-dried to obtain oxidized sodium alginate, i.e., OSA. (4) Preparation of CCZ@OSA / CMCS hydrogel: OSA prepared in step (3) was mixed with carboxymethyl chitosan, and after cross-linking reaction, CCM-Co-ZIF-8 prepared in step (2) was added to obtain CCZ@OSA / CMCS hydrogel; (5) Preparation of CCZ@OSA / CMCS / TA: Spraying tannic acid onto the CCZ@OSA / CMCS hydrogel prepared in step (4) to obtain CCZ@OSA / CMCS / TA.

2. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 1, characterized in that: Step (1) specifically includes the following steps: (1.1) DMF and methanol are mixed in a ratio of 4:1 to prepare a DMF-methanol solution, and 2-methylimidazole is dissolved in the DMF-methanol solution to obtain a 2-methylimidazole solution; (1.2) Dissolve Zn(NO3)2∙6H2O and Co(NO3)2∙6H2O in a DMF-methanol mixture to obtain a mixed solution; (1.3) Mix the 2-methylimidazole solution prepared in step (1.1) with the mixed solution prepared in step (1.2), stir at a speed of 500 to 1000 rpm, and after sufficient reaction, centrifuge to obtain the precipitate, then wash it with methanol at least 3 times, and dry it to obtain Co-ZIF-8 for standby use.

3. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 1, characterized in that: In step (2), the CCM-Co-ZIF-8 preparation method is as follows: pour the Co-ZIF-8 prepared in step (1.3) into anhydrous methanol, ultrasonically disperse it to obtain a Co-ZIF-8 dispersion, then add CCM to the Co-ZIF-8 dispersion, stir evenly, wash with anhydrous methanol and dry it to obtain CCM-Co-ZIF-8.

4. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 1, characterized in that: Step (3) specifically includes the following steps: (3.1) Disperse SA in anhydrous ethanol and stir to form a suspension; Add NaIO4 in an amount equal to that of SA substance into pure water and fully dissolve it to obtain NaIO4 solution; Subsequently, the suspension was mixed with a NaIO4 solution, and reacted in the dark for 5 to 6 hours at room temperature, and ethylene glycol in an amount equal to that of the NaIO4 was added to terminate the reaction, thereby obtaining a reaction mixture; (3.2) The reaction mixture of step (3.1) was poured into anhydrous ethanol and allowed to stand for precipitation. The supernatant was discarded, and the lower precipitate was placed in a dialysis bag with a molecular weight cutoff of 3500Da and dialyzed for at least 3 days. The dialysate was collected and freeze-dried to obtain OSA.

5. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 4, characterized in that: Step (4) specifically includes the following steps: (4.1) preparing a carboxymethyl chitosan solution with a concentration of 0.1 g / mL, and mixing the OSA prepared in step (3.2) with the carboxymethyl chitosan solution in a mass ratio of 1:(1 to 1.5) to obtain an OSA-CMCS hydrogel; (4.2) Prepare a CCM-Co-ZIF-8 solution with a concentration of 100 ug / mL, and mix it evenly with the OSA-CMCS hydrogel prepared in step (4.1) at a mass ratio of 1:1 to obtain a hydrogel loaded with CCM-Co-ZIF-8, namely, CCZ@OSA / CMCS hydrogel.

6. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 5, characterized in that: In step (5), the CCZ@OSA / CMCS / TA hydrogel preparation method is as follows: spraying 2.5%-5% tannic acid by mass onto the CCZ@OSA / CMCS hydrogel prepared in step (4.2), and after sufficient reaction, obtaining a hydrogel with a double cross-linked network structure loaded with curcumin, i.e., CCZ@OSA / CMCS / TA hydrogel.

7. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 3, characterized in that: The mass ratio of the Co-ZIF-8 dispersion to CCM is 1:(1-3).

8. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 2, characterized in that: In step (1.2), the mass ratio of Zn(NO3)2∙6H2O to Co(NO3)2∙6H2O is 1:(1-1.5).

9. The method for preparing a multifunctional bioactive composite hydrogel based on nanoparticles according to claim 2, characterized in that: In step (1.3), the volume ratio of the 2-methylimidazole solution to the mixed liquid is 1:(1-1.5).

10. Use of the hydrogel according to any one of claims 1 to 9 for preparing a chronic wound healing medicament.